Analisis dan Implementasi Protokol Otentikasi FIDO U2F - Sunderi Pranata; Hargyo Tri Nugroho; Hirofumi Yamaki (Ultima Computing : Jurnal Sistem Komputer, 2017)
It is known that password itself is not enough for formidable authentication method since it has a lot of vulnerabilities. Multi factor authentication (MFA) is introduced for the next generation for good authentication to address that issue. MFA combines two or more of three principles of good security, “something you know”, “something you have”, and “something you are”. Most MFA mechanisms work as one time passwords (OTP). However, they can still be vulnerable to phishing and MiTM attack. On top of that, OTP can be hard to use as it requires user to input another password given by the device (SMS, token, authenticator). Implemented in small USB U2F device, FIDO U2F delivers easier yet stronger security on authentication process which implements public key cryptography, challenge-response protocol, and phishing and MitM protection. Index Terms— Authentication protocol, FIDO U2F, Multi factor authentication, OTP